KONTROVERSI PENAFSIRAN ATAS AYAT AL-QUR’AN TENTANG SYAHWAT - Shohibul Azka; Nur Rofiah; Zakaria Husin Lubis (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The issue of women continues to be a hot topic for discussion. One aspect of this is the social stigma that women are often perceived as temptresses, liars, skilled in deception, and sources of scandal. This stigma persists in society. Some verses, such as Qs. Ali Imran/3:14 and Qs. Yusuf/12:28, are frequently used as justification. These two verses are generally associated with lust, which is often understood as something negative and only attributed to women. This paper presents research results on two opposing interpretations of these verses and then analyzes the strengths and weaknesses of each interpretation and their impact on the welfare of both men and women. This research is a library study, where the authors collect data from two conflicting interpretations of the verses and then analyzes and presents it using qualitative methods. The authors also apply the theory of al-Dakhîl and the theory of Mubâdalah. Based on the theory of al-Dakhîl, distortions in the interpretation of lust and inconsistencies in connecting the verses are found dan based on the theory of Mubâdalah, it is found that both men and women possess lust, as lust is a natural disposition in every human being. It can be good or bad, depending on how it is managed. The goodness or badness of lust cannot be attributed to only one gender, as both men and women can have the same potential.